Safety and efficacy considerations amongst the elderly population in the updated treatment of heart failure: a review. (3rd July 2022) - Adams, Jack; Mosler, Charles
ABSTRACT: Introduction: Heart failure is one of the cardiovascular diseases that impacts the geriatric population. As new clinical trials investigating heart failure are conducted, groundbreaking information is assessable to further evolve the treatment. To correctly improve the quality of life of elderly patients, it is critical to evaluate the safety and efficacy of new and improved therapy regimens. Areas covered: In reviewal of the 2021 and 2022 updated guidelines, the safety and efficacy of the newly indicated medications will be addressed. The new indications cover sacubitril/valsartan and two SGLT2 inhibitors: dapagliflozin and empagliflozin. An introduction to the medications discussed covers the pharmacology before addressing the efficacy and safety considerations in the elderly population. Furthermore, prime drug-drug interactions associated with the two classes of medications will be considered as well as providing possible solutions to further create the safest drug therapy for geriatric patients with common comorbidities. Expert Opinion: The two classes of medications, the ARNI and SGLT2 inhibitors, are well-tolerated amongst the elderly population. With the release of new guidelines, the updated medications will provide safer and better therapy in this disease state for geriatrics. One major limitation includes the high cost of these brand-named medications.